A cross-cultural analysis of Flickr users from Peru, Israel, Iran, Taiwan and the UK. (1st July 2010) - Dotan, Amir; Zaphiris, Panayiotis
In this paper, we describe a study exploring cultural differences in user-generated content websites using Flickr, a popular social photo-sharing site, as a case study. The increased popularity of socially driven websites has created new challenges with regard to cross-cultural system design and localisation. This research aimed to identify some of these challenges and help bring cross-cultural usability studies up-to-date with the latest trends on the internet. It also sought to explore the usefulness of Geert Hofstede's popular cultural model for studies of this sort. Findings reveal differences as well as similarities regarding tagging patterns and use of language to annotate content between the five chosen national cultures. These insights could inform the future localisation and internationalisation of user-generated content driven sites like Flickr and You Tube.